CANELC: constructing an e-language corpus - Knight, Dawn; Adolphs, Svenja; Carter, Ronald (Edinburgh University Press, 2014)
This paper reports on the construction of CANELC: the Cambridge and Nottingham e-language Corpus.3 CANELC is a one million word corpus of digital communication in English, taken from online discussion boards, blogs, tweets, emails and SMS messages. The paper outlines the approaches used when planning the corpus: obtaining consent; collecting the data and compiling the corpus database.